Muslim prayer movements as an alternative therapy in the treatment of erectile dysfunction: a preliminary study. - Ibrahim, F.; Sian, T.C.; Shanggar, K.; Razack, A.H. (2013)
[Purpose] Our objective was to assess the effect of salat and mimicking salat movements and postures on subjects with erectile dysfunction. [Methods] Ten volunteers were recruited in this study. Subjects who were Muslims (Group I) were asked to perform their daily salat and a new intervention of an additional 12 movement cycles of salat for three sessions a week. Non-Muslim subjects (Group II) were taught to mimic salat movements, and were asked to perform a total of 12 movement cycles without reading the recitation for three sessions a week. An International Index for Erectile Function 5 (IIEF-5) questionnaire was given to the subjects before and after the intervention of performing salat or mimicking salat movements and postures. A nocturnal electrobioimpedance volume assessment (NEVA) device was used to measure the nocturnal penile tumescence (NPT) parameters over two consecutive nights. A nonparametric test was conducted to find the significant NPT parameters. [Results] The results showed that all measured parameters improved significantly, with the largest change observed in the maximum percent volumetric change over the baseline (from 138 to 222%). [Conclusion] This preliminary study suggests that the alternative approach of salat and mimicking salat movements and postures, may have beneficial effects for ED patients.